(untitled) (Al-Qamar, 2020)
The importance of children’s literature has increased in today’s society. It’s critical to a child’s development of a positive outlook on life. Many writers from various cultures and languages have contributed to it. The main focus of this study is on Syrian authors’ contributions to children’s literature. This aims to critically examine children’s literature in order to find out what makes it better than other works.